2022
DOI: 10.1002/pits.22796
|View full text |Cite
|
Sign up to set email alerts
|

Parental attitude and Instagram addiction: The mediating role of obsessive‐compulsive disorder

Abstract: The study examined the relationship between democratic, authoritarian, and protective-demanding parental attitudes, obsessive-compulsive disorder (OCD), and Instagram addiction. It is based on the correlational research design in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Accordingly, the prevalence of digital gaming disorder is between 1.3% and 9.9% worldwide (WHO, 2022). However, it is reported that the rate of digital gaming disorder has increased more rapidly among adolescents both during and after COVID-19 as a result of, with the increase in the isolation process of the individual at home, the decrease in the face-to-face communication and the greater involvement of digital technologies (Avci et al, 2023;Meng et al, 2022). Therefore, the current monitoring of digital gaming disorder in today's youth and the investigation of its causes and consequences are important in solving this behavioural disorder (González-Cabrera et al, 2022;Yu et al, 2022).…”
Section: Digital Game Addiction In Adolescentsmentioning
confidence: 99%
“…Accordingly, the prevalence of digital gaming disorder is between 1.3% and 9.9% worldwide (WHO, 2022). However, it is reported that the rate of digital gaming disorder has increased more rapidly among adolescents both during and after COVID-19 as a result of, with the increase in the isolation process of the individual at home, the decrease in the face-to-face communication and the greater involvement of digital technologies (Avci et al, 2023;Meng et al, 2022). Therefore, the current monitoring of digital gaming disorder in today's youth and the investigation of its causes and consequences are important in solving this behavioural disorder (González-Cabrera et al, 2022;Yu et al, 2022).…”
Section: Digital Game Addiction In Adolescentsmentioning
confidence: 99%
“…However, there is a need for studies that address many variables that affect them together. Because internet gaming disorder is a problematic behavior that negatively affects the quality of life of young people, this negative cycle can have a negative impact on their social life and academic achievement (Avci et al, 2023). Looking at these variables from a holistic perspective, which can affect the behavior, academic achievement, personality traits, and even the whole lives of young people, who constitute an important part of society today, and therefore university students will contribute to the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The use of social media, which has developed in parallel with the widespread use of mobile devices and the internet, also leads to digital transformation in many areas (Al Halbusi et al, 2022; Avci et al, 2023). According to Al Halbusi et al (2022), the Covid‐19 pandemic has made it somewhat obligatory for individuals to adopt digital technology.…”
Section: Introductionmentioning
confidence: 99%